2001
DOI: 10.1046/j.1442-200x.2001.01353.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic effects of transdermal testosterone for the treatment of microphallus in children

Abstract: When using testosterone ointment as a treatment for microphallus, it should be borne in mind that this application has systemic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In animal models and clinical studies, androgen and estrogen treatments maintained normal insulin sensitivity at physiological concentrations but caused insulin resistance when administered in high doses [48]. Similarly, increased levels of circulating IGF-I were observed after androgen treatment in prepubertal boys [49] and estrogens have also shown to influence the GH/IGF-I axis [50], depending on the administration route. Increases in either hormone can thus lead to a vicious circle of elevated hormone levels [48].…”
Section: Insulin and Igf-i: Correlations With Sex-steroid Hormone Conmentioning
confidence: 98%
“…In animal models and clinical studies, androgen and estrogen treatments maintained normal insulin sensitivity at physiological concentrations but caused insulin resistance when administered in high doses [48]. Similarly, increased levels of circulating IGF-I were observed after androgen treatment in prepubertal boys [49] and estrogens have also shown to influence the GH/IGF-I axis [50], depending on the administration route. Increases in either hormone can thus lead to a vicious circle of elevated hormone levels [48].…”
Section: Insulin and Igf-i: Correlations With Sex-steroid Hormone Conmentioning
confidence: 98%
“…Additionally, both oral and trans-dermal exogenous androgens (42,43) or androgenic progestins (44,45) cause elevations in circulating IGF-I. The effect of exogenous estrogens depends on the route of administration.…”
Section: Effect Of Bmi On Hormone Levelsmentioning
confidence: 99%
“…It has been documented that the development, growth, and maintenance of penile-tissue function is an androgen-dependent process [10]. Clinical and preclinical studies have suggested that abnormalities in the AR, deficiency in 5α-reductase activity, or reduced plasma androgen levels due to the impairment of synthesis of testicular or adrenal androgens, leads to the development of a microphallus [55][56][57][58][59][60][61][62][63]. Grino et al [64] postulated that children with impaired AR function develop micropenises.…”
Section: Role Of Androgens In the Development And Growth Of The Penismentioning
confidence: 99%